2013
DOI: 10.1038/ncomms3750
|View full text |Cite
|
Sign up to set email alerts
|

Transition fibre protein FBF1 is required for the ciliary entry of assembled intraflagellar transport complexes

Abstract: Sensory organelle cilia play critical roles in mammalian embryonic development and tissue homeostasis. Intraflagellar transport (IFT) machinery is required for the assembly and maintenance of cilia. Yet how this large complex passes through the size-dependent barrier at the ciliary base remains enigmatic. Here we report that FBF1, a highly conserved transition fibre protein, is required for the ciliary import of assembled IFT particles at the cilia base. We cloned dyf-19, the C. elegans homolog of human FBF1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
122
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 57 publications
10
122
0
1
Order By: Relevance
“…Multiple components of the centriolar distal appendages have been identified recently, including Ccdc41, Cep89, Sclt1, and Fbf1 (9,11,12,14). To study whether C2cd3 regulates the recruitment of additional distal appendage components, we transiently expressed GFP-tagged Ccdc41, Sclt1, Cep89, and Fbf1 in wild-type and C2cd3 GT mutant cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple components of the centriolar distal appendages have been identified recently, including Ccdc41, Cep89, Sclt1, and Fbf1 (9,11,12,14). To study whether C2cd3 regulates the recruitment of additional distal appendage components, we transiently expressed GFP-tagged Ccdc41, Sclt1, Cep89, and Fbf1 in wild-type and C2cd3 GT mutant cells.…”
Section: Resultsmentioning
confidence: 99%
“…jax.org/marker/MGI:2141942), an inhibitor of ciliogenesis, from the distal end of the mother centriole (10). Recent studies have also suggested that components of the distal appendages are essential for docking ciliary vesicles to the mother centriole (9,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…IFT particles continuously cycling between the cytoplasm and the flagellar compartment are first gathered in a pool at the flagellar base, where they associate with the basal body transitional fibres (Deane et al, 2001;Wei et al, 2013;Wood and Rosenbaum, 2014); from this pool, groups of particles organize into linear arrays -the IFT trains -and periodically enter the flagellum (Dentler, 2005;Ludington et al, 2013). The molecular mechanisms controlling the transit of particles through the transition zone and their organization into trains are largely unknown; similarly, very little is known about the molecular process controlling the reorganization of anterogrademoving trains into those moving in a retrograde manner at the tip, although, in Chlamydomonas, CDPK-1 has been recently implicated in kinesin-II inactivation and dissociation from the IFT-B subcomplex (Liang et al, 2014).…”
Section: Discussion Short Ift Trains Are Involved In Anterograde Tranmentioning
confidence: 99%
“…Cby predominantly clusters around the transition fibers in mature ciliated cells, 15,[34][35][36][37][38][39] which are known to be the sites critical for IFT particle assembly, docking, and entry into the ciliary compartment. 14,21 Interestingly, other transition fiber proteins, such as CEP164 and FBF1, 17,[65][66][67] have also been shown to regulate IFT particle formation and ciliary entry, implying that particularly complex regulation of IFT processes may occur at the transition fibers. Thus, Cby may modulate recruitment of IFT components, assembly of IFT-motor complexes, and their efficient entry into the ciliary compartment at the ciliary base.…”
Section: Discussionmentioning
confidence: 99%